Indian Union and the states - Krishnaswami, A. (Oxford, 1965)
This book embodies the Sir William Meyer Lectures delivered at the University of Madras, early in December 1963. A postcript is included on the developments following the death of Jawaharlal Nehru in May this year. The theme of these lectures is "The Indian Union and the States: A Study in Autonomy and Integration." The approach is partly historical, partly analytical. The author appreciates the privilege given him of presenting this study in the series of Sir William Meyer lectures.
Keywords: Politics & Govt